Scientists’ attitudes about citizen science at Long-Term Ecological Research (LTER) sites - L’Astorina, Alba; Davis, Cathlyn; Pugnetti, Alessandra; Campanaro, Alessandro; Oggioni, Alessandro; Bergami, Caterina (Frontiers in Environmental Science, 2023)
A profound transformation, in recent decades, is promoting shifts in the ways ecological science is produced and shared; as such, ecologists are increasingly encouraged to engage in dialogues with multiple stakeholders and in transdisciplinary research. Among the different forms of public engagement, citizen science (CS) has significant potential to support science-society interactions with mutual benefits. While many studies have focused on the experience and motivations of CS volunteers, scarce literature investigating the perspectives of researchers is available. The main purpose of this paper is to better understand scientists’ attitudes about CS in the context of its potential to support outcomes that extent beyond more traditional ones focused on promoting science knowledge and interest. We surveyed the scientific community belonging to the International Long-Term Ecological Research (ILTER) network because ILTER is of interest to multiple stakeholders and occurs over long time scales. Via an online questionnaire, we asked ILTER scientists about their willingness to participate in different types of public engagement, their reasons for participating in CS, the associated barriers, and any impacts of these efforts on them. Our findings show that many ILTER scientists are open to participating in CS for a wide range of reasons; the dominant ones involve deeper public engagement and collaboration. The barriers of greatest concern of these respondents were the lack of institutional support to start and run a CS project and the difficulty of establishing long-term stable relationships with the public. They reported impacts of CS activities on how they pursue their work and acknowledged the benefit of opportunities to learn from the public. The emerging picture from this research is of a community willing and actively involved in many CS projects for both traditional reasons, such as data gathering and public education, and expanded reasons that activate a real two-way cooperation with the public. In the ILTER community, CS may thus become an opportunity to promote and develop partnerships with citizens, helping to advance the science-society interface and to rediscover and enhance the human and social dimension of the scientific work.